A controllable water signal transistor. Issue 14 (27th March 2017) - Wu, Lili; Zhou, Xiaoyan; Lu, Hangjun; Liang, Qing; Kou, Jianlong; Wu, Fengmin; Fan, Jintu
Abstract : We performed molecular dynamics simulations to study the regulating ability of water chains in a Y-shaped nanochannel. It was shown that a signal at the molecular level could be controlled by two other charge-induced signals when the water chains were confined in a narrow Y-shaped nanochannel. Abstract : We performed molecular dynamics simulations to study the regulating ability of water chains confined in a Y-shaped nanochannel. It was shown that a signal at the molecular level could be controlled by two other charge-induced signals when the water chains were confined in a Y-shaped nanochannel, demonstrating promising applications as water signal transistors in nanosignal systems. The mechanism of a water signal transistor is similar to a signal logic device. This remarkable ability to control the water signal is attributed to the strong dipole-ordering of the water chains in the nanochannel. The controllable water signal process of the Y-shaped nanochannel provides opportunities for future application in the design of molecular-scale signal devices.